CALIDAD VERSUS PRODUCTIVIDAD ¿QUE ES LO PRIMERO? - Vargas, Gustavo A. (1993)
This document refers to some key factors as competitive, technological and organizational which may affect management decisions involved in determining the sequence of quality or productivity. The objective is to try to close the "implementation gap" by studying successful experiences (taken from real life) of companies that faced and over sacked this challenge, and by characterizing the internal and external circumstances to the companies that determined the order of priority of the implementation. The analysis has both logical and empirical bases, detailed in the cases described. Finally, the choice will depend between the challenges a company faces, the resources , and the time context in which it has actions. In conclusion, it is possible to define the profile of companies and their internal/external environments that allow to define the order of priority between productivity and quality, for this there are several implementation guidelines: the set of product-market characteristics such as the product lifecycle and the degree of product diversity and market growth rate, cost leadership and immediate access of the product.